2016
DOI: 10.1080/23744731.2016.1186460
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal convective boiling of R448A, R449A, and R452B within a micro-fin tube

Abstract: This article presents local convective boiling measurements in a micro-fin tube for three low global warming potential refrigerants: R448A, R449A, and R452B1. An existing correlation was modified to predict multi-component mixtures, which predicted 98% of the measurements to within ±20%. The new correlation was used to compare the heat transfer coefficient of the three test fluids at the same heat flux, saturated refrigerant temperature, and refrigerant mass flux. The resulting comparison showed that refrigera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Kedzierski and Kang (2016) provide a correction factor for Eq. (4) to predict the flow boiling Nusselt Number (Nu) for mixtures of any number of refrigerants.…”
Section: Resultsmentioning
confidence: 99%
“…Kedzierski and Kang (2016) provide a correction factor for Eq. (4) to predict the flow boiling Nusselt Number (Nu) for mixtures of any number of refrigerants.…”
Section: Resultsmentioning
confidence: 99%
“…Convective boiling tests were performed on R-448A, R-449A, and R-452B in a microfin tube by Kedzierski and Kang [50], who found that R-452B had a 59% greater HTC than R-448A/R-449A. Matsuse et al [51] conducted an investigation into the flow boiling properties of R-32 inside a horizontal copper circular tube with an inner diameter of 1.0 mm.…”
Section: Boiling Inside the Plain/smooth Tubementioning
confidence: 99%
“…NIST (2021) provides an online database that contains the complete corrected flow boiling heat transfer measurements of the Hamilton et al (2008), the Kedzierski and Park (2013), the Kedzierski and Kang (2016), and the Kedzierski and Kang (2018). The data presented in Domanski et al (2021) is also included in the database; however, it did not require correction.…”
Section: Measurementsmentioning
confidence: 99%
“…The second NIST study (Kedzierski and Park, 2013) contains the refrigerants R134a, R513A and R1234ze(E). The third NIST study (Kedzierski and Kang, 2016) contains the refrigerants R448A, R449A, and R452B. Finally, the fourth NIST study (Kedzierski and Kang, 2018) contains the refrigerants R1234yf, R134a, and R450A.…”
Section: Introductionmentioning
confidence: 99%